PTH 1-34-functionalized bioactive glass improves peri-implant bone repair in orchiectomized rats: Microscale and ultrastructural evaluation - Gomes-Ferreira, Pedro Henrique Silva [UNESP]; Micheletti, Chiara; Frigério, Paula Buzo [UNESP]; Batista, Fábio Roberto de Souza [UNESP]; Monteiro, Naara Gabriela [UNESP]; Bim-júnior, Odair [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Grandfield, Kathryn; Okamoto, Roberta [UNESP] (Elsevier, 2022)
The objective of this work was to investigate the use of Biogran® functionalized with parathyroid hormone (PTH) 1–34 by sonochemistry for the local delivery of this anabolic agent to the implant site. The effects of Biogran® and topical administration of PTH 1–34 on peri-implant bone regeneration were evaluated from the microscale to ultrastructural levels in healthy (SHAM) and orchiectomized (ORQ). While some animals only received a titanium implant in their tibial metaphyses (CLOT group), in others the peri-implant defect was first filled with Biogran® either without or with PTH 1–34 functionalization (BG and BGPTH groups, respectively) prior to implant installation. Osseointegration was characterized from a biomechanical perspective by measuring the removal torque with the counter-torque technique. Micro-CT was used to evaluate the percentage of bone volume, trabecular thickness, number and separation, and bone-implant contact (BIC). Dynamics of new bone formation were assessed by measuring fluorochrome area, daily mineral apposition rate, and neoformed bone area using confocal laser microscopy. RT-PCR was performed to evaluate ALP and osteocalcin expression. The interface between newly formed bone and Biogran® was examined using scanning electron microscopy (SEM) and scanning transmission electron microscopy (STEM) at the micro-and nanoscale, respectively, while elemental analyses were completed in SEM with energy-dispersive X-ray spectroscopy (EDS). STEM imaging demonstrated the intimate attachment of bone to Biogran® (nanoscale level). Overall, the results suggest that the effectiveness of the topical administration of PTH 1–34 at the implant site seems enhanced in osteoporotic bone, promoting peri-implant bone regeneration to comparable levels in healthy conditions.
Keywords: Bioactive glass; Bone regeneration; Dental implants; Local drug delivery; Osteoporosis; Parathyroid hormone